2023
DOI: 10.3390/su151511792
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood Identity Formation and the Changes in an Urban Regeneration Neighborhood in Gwangju, Korea

Hae Young Yun,
Hyun-ah Kwon

Abstract: Since the Urban Regeneration Act in 2013, central and local Korean governments have endeavored to regenerate deprived urban neighborhoods. This study analyzed how these efforts have changed the nature of neighborhood identity in Yanglim, Gwangju, Korea. The authors analyzed 62,386 Naver blog posts from 2013 to 2022, utilizing an Artificial Intelligence (AI) technique, Topic Modeling (i.e., Latent Dirichlet Allocation). Using trend analysis by topic, three phases were identified: (1) Phase 1: Flourishment (Janu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Therefore, wherever people are living together, there will be neighborhood spaces. The studies on the physical and meaning characteristics of neighborhood spaces apply to urban people and urban areas [10,11], as well as to rural areas and rural older people. Recent studies showed that neighborhood space is essential in the emotional support of rural people, especially older people.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, wherever people are living together, there will be neighborhood spaces. The studies on the physical and meaning characteristics of neighborhood spaces apply to urban people and urban areas [10,11], as well as to rural areas and rural older people. Recent studies showed that neighborhood space is essential in the emotional support of rural people, especially older people.…”
Section: Introductionmentioning
confidence: 99%